Art of living - "Lebell, Sharon" (New Delhi, 2005)
Epictetus was born into slavery about 55 CE in the Eastern outreaches of the Roman Empire. Once freed, he established an influential school of stoic philosophy, stressing that human beings cannot control life, only their responses to it. By putting into practice the ninety-three witty, wise, and razor-sharp instructions that make up the art of living, readers learn to meet the challenges of everyday life successfully and to face life's inevitable losses and disappointments with grace.
Keywords: Spiritual life